The Effect of Investment Efficiency toward Economic Growth in South Sumatera and Jambi Province - Feny Marissa; Anna Yulianita; Annisa Fitriyah (Department of Development Economics, Universitas Sriwijaya, 2019)
The study aims to measure and compare the efficiency level of investment to boost economic growth in South Sumatera and Jambi Province. This study use quantitative approach with time series data between 2007 to 2016 from the Central Bureau of Statistic (BPS) and publication related to the study. The efficiency of investment was measured by Incremental Capital Output Ratio (ICOR) approach and analyzed using Ordinary Least Square (OLS). The study indicates that (1) the relationship between investment efficiency which measured by ICOR approach and economic growth of each provinces (South Sumatera and Jambi) is negative; (2) this research show that investment efficiency in Jambi Province give more effect to its economic growth than South Sumatera and Jambi Province has grown better than South Sumatera Province in the same development stage without an increase in the proportion of investment to Gross Domestic Regional Product.